Analisis Morfologi Fi’il Madhi Dan Fi’il Mudhori Pada Ayat Al-Qur’an Surat An-Naba Juz 30 - Ghofur, M. Abdul; Fadholi, Amak; Tauhid, M. Halim (UAS PRESS, 2024)
Written, spoken, and arbitrary, Arabic has a distinct language style. In the same way, there are many domains for Arabic knowledge. You'll be exposed to a wide range of subjects when studying Arabic. Morphology, often known as shorof science, is one genre. In terms of morphology, the goal of this study is to characterise the linguistic features of surah An-Naba' in the Qur'an. Library research is the method used in this kind of study. This research seeks to determine the number of fi'il mudhori in Surah An-naba juz 30 and their reading pattern, in addition to identifying the dhomir that appears in each fi'il mudhori sentence. And describes in terms of the nahwu and shorof science approaches. The research results illustrate that researchers found 16 words that included fiil mudhari, these 16 words had been included in several different wazans and dhomir-dhomir.